Tempe Production Business in Community Empowerment at Sodong Company, Tangerang - Purnawan , Lesna; Mulyana, Achmad; Setiawan, Aries; Kala Kusumajati, Wisnu; Riyanto , Slamet (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to explore the efforts and challenges faced by tempe producers in community empowerment. It employs a qualitative descriptive approach and uses both primary and secondary data. Data collection methods include observation, in-depth interviews with respondents, and document analysis. Data analysis techniques involve data reduction, data presentation, and data verification. The findings indicate that: (1) There are ongoing efforts to empower the community in Tangerang Regency, particularly through Sodong Trading's tempe production initiative. The company recruits two men and four women, providing them with raw soybeans and step-by-step theoretical training on tempe production, progressing from beginner to independent production. The training emphasizes practical, hands-on experience, including how to manage and market the tempe, with average monthly production increasing over time. As a result, the economic conditions of the community have improved. (2) However, the main challenge faced by the tempe producers is the availability of raw materials, particularly soybeans. Imported soybeans are often difficult to obtain, while local soybeans are insufficient and expensive.